2020
DOI: 10.1016/j.sleep.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an individualized exercise training program on severity markers of obstructive sleep apnea syndrome: a randomised controlled trial

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…In line with previous studies 46 , 47 , ET also caused an improvement in the severity of OSA. The observation that exercise changed arousals and AHI demonstrates that ET improves sleep pattern in patients with OSA.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies 46 , 47 , ET also caused an improvement in the severity of OSA. The observation that exercise changed arousals and AHI demonstrates that ET improves sleep pattern in patients with OSA.…”
Section: Discussionsupporting
confidence: 93%
“…The main findings revealed that 6 weeks of this combination program was able to ameliorate EDS, lower the risk of SRBDs, improve most of the anthropometric variables, and increase physical fitness in adults with obesity and SRBDs. These results are similar to previous studies which showed an improvement in sleep quality 7 , 10 , 11 , 12 , 25 , 26 , 27 , and sleep indices 12 , 25 , 28 after completion of exercise programs. However, the study period for those studies was longer than the present study, excepted for the study of Ebrahimi et al (2017) 27 which examined the effect of yoga and aerobic exercise at week 6 and week 12.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the exercise prescription of those previous studies was performed differently to our study. For example, some studies used individual aerobic exercises (AE) 7 , AE plus RT 12 , diet and AE combined with RT 10 , home-based combination program for the aging 11 , and lifestyle modification including diet and physical activity 7 , 29 . There were limited studies using a HIIT program for SRBDs patients 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 For example, PA has positive effects on AHI in terms of rapid eye movement (REM) and non-REM sleep, subjective sleepiness, cardiometabolic risk factors associated with OSA, and VO2peak, which is associated with a significant survival benefit. 11 14 However, individuals with OSA report low levels of PA and have low aerobic capacity. 11 Their symptoms may hamper daily life activities in several ways, and PA appears to decrease with increasing AHI.…”
Section: Introductionmentioning
confidence: 99%